2017
DOI: 10.1590/0037-8682-0450-2016
|View full text |Cite
|
Sign up to set email alerts
|

Profile of HIV subtypes in HIV/HBV- and HIV/HCV-coinfected patients in Southern Brazil

Abstract: Introduction: HIV and viral hepatitis infections are major causes of chronic disease worldwide and have some similarities with regard to routes of transmission, epidemiology, front barriers faced during access of treatment, and strategies for a global public health response. The objective was to describe the HIV-1 subtypes, viral tropism and single-nucleotide polymorphisms (SNPs) of interleukin 28B (IL28B) from a case series of HIV/viral hepatitis coinfected patients from southern Brazil. Methods: Clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our study corroborates the results of these studies. In addition, the results of the present study were in accordance with previous investigations, which report that B recombinant and CRFs of HIV-1 circulate among HIV-coinfected patients (12,35) . The detailed dynamics of HIV subtypes viral propagation in the study region is not well understood, although two phylogeographic studies have demonstrated possible routes for the origin and spread of subtype C in the Southern region of the country (36,37) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study corroborates the results of these studies. In addition, the results of the present study were in accordance with previous investigations, which report that B recombinant and CRFs of HIV-1 circulate among HIV-coinfected patients (12,35) . The detailed dynamics of HIV subtypes viral propagation in the study region is not well understood, although two phylogeographic studies have demonstrated possible routes for the origin and spread of subtype C in the Southern region of the country (36,37) .…”
Section: Discussionsupporting
confidence: 93%
“…However, there have been a few studies showing the genetic variability of HIV-1 among patients with HIV-hepatitis coinfections. A study in HIV-coinfected patients in Brazil reported that HIV-1 subtype C and B were present in 47.4% and 31.6% of HIV-coinfected patients, respectively (35) ; another Brazilian study reported that HIV-1 subtype B was the most prevalent (12) . Our study corroborates the results of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant HIV-1 subtype was subtype B. A study from Brazil showed that the major subtypes of HBV/HIV and HCV/HIV co-infection were subtypes B and C, respectively (27). Different subtypes may be seen in circulation in Turkey, especially in the cosmopolitan cities, because Turkey is a country that receives immigrants daily.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, other CCR5 blockers (e.g., cenicriviroc, leronlimab) are being tested to treat HIV infection and other inflammatory conditions, and maraviroc emerges as a potential drug to treat other diseases involving CCR5, especially some types of cancer (77). In Brazil, CCR5 blockers represent a good choice for HIV treatment, since most of the circulating viral strains show CCR5 tropism (78)(79)(80). Based on the scenario presented above, Figure 1 shown an alluvial diagram representing the classic outcomes associated with the CCR5D32, including "desirable" and "undesirable" effects.…”
Section: Pivotal Information Regarding the Ccr5d32 Variantmentioning
confidence: 99%